Mechatronics / Dan Necsulescu. - Necsulescu, D. S. (Dan S.) (Prentice Hall, 2002)
Designed for a first course in mechatronics taught at final-year level in departments of mechanical, electrical, computer and general engineering, this text provides a self-contained, modern treatment of computer-based, mixed-systems integration.